2017
DOI: 10.1007/s11060-017-2535-4
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional analysis from a single institution’s experience of psychosocial distress and health-related quality of life in the primary brain tumor population

Abstract: Primary brain tumor patients experience high levels of distress. The purpose of this cross-sectional, retrospective study is to evaluate the level and different sources of psychosocial distress and how these pertain to health-related quality of life (HRQoL). The Primary and Recurrent Glioma registry at Duke's The Preston Robert Tisch Brain Tumor Center was queried retrospectively for demographic and clinical information on patients seen between December 2013 and February 2014. Data also included the National C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…In this small patient collection with the cut-off DT ≥ 5, 74.4% patients demonstrated suspicious striking results [ 1 ]. Our larger study demonstrated comparable high positive rates, in line also with reports by other authors [ 5 , 15 , 16 ]. Due to the ongoing discussion about the “correct” cut-off value in DT in brain tumor patients with values ranges from ≥4 to ≥6 [ 4 ], we assessed sensitivity and specificity with DT ≥5 and DT≥6.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this small patient collection with the cut-off DT ≥ 5, 74.4% patients demonstrated suspicious striking results [ 1 ]. Our larger study demonstrated comparable high positive rates, in line also with reports by other authors [ 5 , 15 , 16 ]. Due to the ongoing discussion about the “correct” cut-off value in DT in brain tumor patients with values ranges from ≥4 to ≥6 [ 4 ], we assessed sensitivity and specificity with DT ≥5 and DT≥6.…”
Section: Discussionsupporting
confidence: 93%
“…Patients experience sadness; they feel ashamed of their diagnosis, appearance, or resulting deficits and withdraw more and more from social life. Up to 74% of patients report increased distress [ 1 ] with physical and emotional issues [ 2 , 3 ], resulting in reduced quality of life [ 4 , 5 ]. Up to 15-38% of the patients develop depressive symptoms [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health-related quality of life (HRQOL) is a medical concept developed in recent years that means an individual's or a group's perceived physical and mental health over time [4][5][6]. Recently, numerous researches have reported that the patients' HRQoL significantly decreased because of brain cancer [7,8]. The main reason is that different from other cancers, brain cancer can cause personality changes and cognitive decline because of its position [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Common symptoms, regardless of tumor type, size, and location, include fatigue, memory impairment, distress, and sleep disturbance. [1][2][3] These symptoms not only occur concurrently, but are also known to adversely affect quality of life. The interrelated nature of symptoms suggests that addressing one symptom may contribute to improvement in other areas, making an argument for targeted symptom management.…”
Section: Introductionmentioning
confidence: 99%